Aurelius Prudentius Clemens and the emergence of martyr cult in Caesaraugusta: An Analysis of Peristephanon 4 (Salduie, 2022)
This paper analyses the emergence of the cult of martyrs and relics in Caesaraugusta as attested to by Prudentius in Perist. 4. Aged and retired from a post at the court of Milan, Prudentius decided to reinforce the new martyr cult he had experienced in Italy bycomposing Peristephanon. As a lay writer and client of the of episcopal house of the Valerii, Prudentius inspires in oral tradition as well as in emergent hagiography. He then features the Eighteen Martyrs as Christ’s soldiers and merges the traits of Vincent’s passion with that of the Roman deacon Lawrence. As regards Encratis, she is introduced as an example of male virtue and as a peculiar case of living martyr. Her character suffuses traits both of the modest virgin Agnes and the new ideal of confessors and ascetics. If compared to other sources, Perist. 4 proves to be fundamental both to later passiones and to the history and archaeology of Christian Caesaraugusta.
Keywords: Prudentius; Peristephanon 4; Caesaraugusta; martyr cult; Encratis; Vincent; Eighteen Martyrs